Analysis of the Role of Satisfaction in Mediating the Influence of Fastron Series Lubricant Products on Customer Loyalty - Kushariyadi Kushariyadi (Jurnal Wacana Ekonomi, 2026)
Business developments in the era of globalization have led to increasing competition in the national lubricant industry. This condition requires companies to be able to maintain and increase customer loyalty to the products offered. Customer loyalty can be formed when consumers feel satisfied after using the product, while satisfaction itself is largely influenced by consumer perceptions of product quality. In this study, this relationship is analyzed to determine the extent to which the quality of Fastron Series products influences customer loyalty with satisfaction as a mediating variable. The research method uses a quantitative approach with data processing through multiple linear regression using SPSS software. The data collection technique was carried out by distributing questionnaires to respondents using accidental sampling. The study population was Fastron Series product users at PT Pertamina Lubricants Marketing Operation Region (MOR) IV Semarang. The findings of this study are expected to provide a basis for consideration for companies in strategies to improve product quality and build customer loyalty.